a) 3/x =5/7 c) 5/6 = 1+t/10 e) 2x-5/3 = 4/5 b) 8/3,5 = 4/y d) 1/z-1 = 6,5/8 f) 10/1,5 = 8/9-3x
a) 3/x =5/7 /*x x ≠ 0
3 = 5/7*x
-5/7x = -3 /*7
-5x = -21 /:(-5)
x = 4,2
c)
5/6 = 1+t/10 /*30
25 = 30 + 3t
-3t = 5 /:(-3)
t = - 5/3
e) 2x-5/3 = 4/5 /*15
30x - 25 = 12
30x = 37 /:30
x = 37/30
b) 8/3,5 = 4/y
8/1 : 7/2 = 4/y
8/1 * 2/7 = 4/y
16/7 = 4/y /*y y ≠ 0
16/7y = 4 /*7
16y = 28 /:16
y = 1,75
d) 1/z-1 = 6,5/8
1/z - 1 = 13/2 : 8/1
1/z - 1 = 13/2 * 1/8
1/z - 1 = 13/16
1/z = 0,8125 + 1
1/z = 1,8125 /*z z ≠ 0
1 = 1,8125z
-1,8125z = -1 /:(-1,8125)
z = -1/1 : (-29/16) = -1/1 *(-16/29) = 16/29
z = 16/29
f) 10/1,5 = 8/9-3x
10:3/2 = 8/9 - 3x
10/1 : 3/2 = 8/9 - 3x
10/1 * 2/3 = 8/9 - 3x
20/3 = 8/9 - 3x /*9
60 = 8 - 27x
27x = - 52 /:27
x = - 52/27
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a) 3/x =5/7 /*x x ≠ 0
3 = 5/7*x
-5/7x = -3 /*7
-5x = -21 /:(-5)
x = 4,2
c)
5/6 = 1+t/10 /*30
25 = 30 + 3t
-3t = 5 /:(-3)
t = - 5/3
e) 2x-5/3 = 4/5 /*15
30x - 25 = 12
30x = 37 /:30
x = 37/30
b) 8/3,5 = 4/y
8/1 : 7/2 = 4/y
8/1 * 2/7 = 4/y
16/7 = 4/y /*y y ≠ 0
16/7y = 4 /*7
16y = 28 /:16
y = 1,75
d) 1/z-1 = 6,5/8
1/z - 1 = 13/2 : 8/1
1/z - 1 = 13/2 * 1/8
1/z - 1 = 13/16
1/z = 0,8125 + 1
1/z = 1,8125 /*z z ≠ 0
1 = 1,8125z
-1,8125z = -1 /:(-1,8125)
z = -1/1 : (-29/16) = -1/1 *(-16/29) = 16/29
z = 16/29
f) 10/1,5 = 8/9-3x
10:3/2 = 8/9 - 3x
10/1 : 3/2 = 8/9 - 3x
10/1 * 2/3 = 8/9 - 3x
20/3 = 8/9 - 3x /*9
60 = 8 - 27x
27x = - 52 /:27
x = - 52/27